The Effect of Progressive Muscle Relaxation on the Level of Anxiety Congestive Heart Failure Functional Class I And II in the Hospital of Internal Disease of Dr. Slamet Garut - Sulastini, Sulastini; Mediani, Henny Suzana; Fitria, Nita; Nugraha, Bambang Aditya (Jurnal Keperawatan Soedirman, 2019)
Anxiety is major psychological problem in congestive heart failure (CHF) patients. Anxiety leads to reduced quality of life. Anxiety can be treated using non phamacologic intervention. One of the interventions is progressive muscle relaxation (PMR). PMR is the most simple relaxation technique and possible to be applied in CHF patient. This study aimed to determine the effect of progressive muscle relaxation on anxiety IN CHF patients in dr. Slamet Garut hospital. This study used quasi-experimental design pretest and posttest with control group. Samples were selected using consecutive sampling technique (23 patients for each group). Hamilton Anxiety Rating Scale (HARS) was used to measured anxiety. Data were analyzed by Wilcoxon test and Mann-Whitney test. Analysis showed that there was a significant decrease in the mean anxiety score pre and post test both in the intervention and control group (p=0.000) and a significant difference in mean anxiety score reduction between groups (p=0.017) This study concluded that progressive muscle relaxation was effective to reduce anxiety levels in CHF patients. Nurses can apply progressive muscle relaxation as a complementary therapy to reduce anxiety in CHF patients